SISTEM INFORMASI PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA PARUH WAKTU (SIPATUH) BERBASIS WEB DI BKPSDM KABUPATEN GORONTALO - Stevie Eka Putri Lamato; Wahyudin Hasyim; Hilmansyah Gani; Alter Lasarudin (Akademika : Jurnal Ilmiah Media Publikasi Ilmu Pengetahuan dan Teknologi, 2026)
This research aims to design and develop a Government Employee Information System with Work Agreements (SIPATUH) to improve the effectiveness and efficiency of Part-Time PPPK data management and support digital archiving. The challenges faced include manual data processing, which leads to errors, delays, difficulty in data retrieval, and the accumulation of physical files that are at risk of damage and loss. The Waterfall model was used, encompassing requirements analysis, design, implementation, and testing. The system was developed using JavaScript and MySQL and tested using Black Box Testing. The results indicate that the system simplifies data management, improves accuracy, and accelerates information retrieval and presentation. Therefore, SIPATUH is expected to improve data management performance and support the implementation of digital archiving